A clinicopathological study of triple-negative breast carcinoma in a patient cohort from a tertiary care center in Sri Lanka - Harshima D Wijesinghe; Janakie Fernando; Upul Senarath; Gayani K Wijesinghe; Menaka D S. Lokuhetty (Wolters Kluwer Medknow Publications, 2020)
Background: Triple negative breast carcinoma (TNBC) and basal-like breast carcinoma (BLBC) are subtypes of breast carcinoma (BCa) that are associated with poor survival. Aims: To study the prevalence, clinicopathological profile and survival of TNBC among a Sri Lankan patient cohort and to determine the proportion and predictive histological features of BLBC among TNBCs. Study Setting and Design: A cohort of 221 women undergoing primary surgery for BCa at a tertiary-care center in Sri Lanka was studied. Materials and Methods: Clinicopathological and follow-up information were collected by patient interviews and review of slides and clinical records. Estrogen, progesterone, HER2 receptors, and basal markers (CK5/6, CK14, EGFR, 34βE12) were evaluated immunohistochemically. Statistical Analysis: Data was analyzed with Chi-square test, multinomial logistic regression, and Cox regression using SPSS20.0. Results: Fifty-three (24%) tumors were triple-negative (95%CI = 18.37%-29.63%). On multivariate analysis, young age (P = 0.002), high Nottingham grade (P = 0.005), moderate to severe tumor necrosis (P = 0.004), absent ductal carcinoma in situ (DCIS) (P = 0.04), reduced vascular density at tumor edge (P = 0.016) and distinct cell margins (P = 0.047) predicted TNBC over luminal subgroups, whereas reduced vascular density (P = 0.004) and low TNM stage (P = 0.011) distinguished TNBC and HER2. BLBC accounted for 45.28% (95%CI 32.66%-58.55%-24/53) of TNBC. The presence of extensive necrosis in TNBC correlated significantly with BLBC (P = 0.03). The survival among the TNBC subgroup did not differ significantly from other subgroups. Conclusion: Twenty four percent were TNBCs by immunohistochemical analysis, comparable to studies in the Indian subcontinent, however higher than the West. TNBC status correlated with younger age, high tumor grade, necrosis, absent DCIS, reduced vascular density at tumor edge, and distinct cell margins. The presence of moderate to extensive necrosis in TNBC was predictive of BLBC.